Behavioral Analysis of Vendors and the Presence of Lead in Fried Snacks Sold Around Mandonga Mall Street Using Atomic Absorption Spectrophotometry - I Kadek Sudarsana; Yasnani Yasnani; La Ode Ahmad Saktiansyah Saktiansyah; Hartati Bahar; Ramadhan Tosepu (Journal of Health Science and Pharmacy, 2024)
Background: Fried snacks are a popular type of street food among the public. Lead from vehicle emissions is one of the pollutants commonly found in street food sold along the roadside. Although the level of lead pollution in the air of Kendari City remains below the permissible threshold, its levels continue to rise annually, posing potential health risks. Objective: This study aims to analyze vendor behavior concerning the presence of lead in fried snacks sold around Mandonga Mall Street. Method: This research employs an experimental design with laboratory tests conducted using the Atomic Absorption Spectrophotometry (AAS) method. The population consists of all fried snack vendors around Mandonga Mall Street, totaling 10 individuals. Sampling was conducted using the total sampling method. Results: The study revealed that all 10 samples tested (100%) contained lead; however, the levels were below the threshold set by BPOM RI Regulation No. 5 of 2018 (0.25 ppm). The detected lead levels ranged from 0.0002 ppm to 0.0022 ppm, with an average of 0.001 ppm. Additionally, the findings showed that 7 vendors (70%) had sufficient knowledge about the dangers of lead, while 3 vendors (30%) had limited knowledge. All vendors (100%) exhibited negative attitudes toward the hazards of lead. Conclusion: The study concludes that lead was present in all tested samples. Although the levels were below the regulatory threshold, vendors’ knowledge about lead hazards was relatively adequate, but their attitudes toward its dangers were negative. Keywords: Lead, Fried Snacks, Knowledge, Attitude, Atomic Absorption Spectrophotometry, Indonesia